Peripherally delivered hepatopreferential insulin analog insulin‐406 mimics the hypoglycaemia‐sparing effect of portal vein human insulin infusion in dogs. Issue 10 (8th July 2019) - Gregory, Justin M.; Kraft, Guillaume; Scott, Melanie F.; Neal, Doss W.; Farmer, Ben; Smith, Marta S.; Hastings, Jon R.; Madsen, Peter; Kjeldsen, Thomas B.; Hostrup, Susanne; Brand, Christian L.; Fledelius, Christian; et al.
Abstract: Aims: We previously quantified the hypoglycaemia‐sparing effect of portal vs peripheral human insulin delivery. The current investigation aimed to determine whether a bioequivalent peripheral vein infusion of a hepatopreferential insulin analog, insulin‐406, could similarly protect against hypoglycaemia. Materials and methods: Dogs received human insulin infusions into either the hepatic portal vein (PoHI, n = 7) or a peripheral vein (PeHI, n = 7) for 180 minutes at four‐fold the basal secretion rate (6.6 pmol/kg/min) in a previous study. Insulin‐406 (Pe406, n = 7) was peripherally infused at 6.0 pmol/kg/min, a rate determined to decrease plasma glucose by the same amount as with PoHI infusion during the first 60 minutes. Glucagon was fixed at basal concentrations, mimicking the diminished α‐cell response seen in type 1 diabetes. Results: Glucose dropped quickly with PeHI infusion, reaching 41 ± 3 mg/dL at 60 minutes, but more slowly with PoHI and Pe406 infusion (67 ± 2 and 72 ± 4 mg/dL, respectively; P < 0.01 vs PeHI for both). The hypoglycaemic nadir ( c . 40 mg/dL) occurred at 60 minutes with PeHI infusion vs 120 minutes with PoHI and Pe406 infusion. ΔAUCepinephrine during the 180‐minute insulin infusion period was two‐fold higher with PeHI infusion compared with PoHI and Pe406 infusion. Glucose production (mg/kg/min) was least suppressed with PeHI infusion (Δ = 0.79 ± 0.33) and equally suppressed with PoHI and Pe406 infusion (Δ = 1.16 ± 0.21 and 1.18 ± 0.17, respectively; P = NS). Peak glucose utilization (mg/kg/min) was highest with PeHI infusion (4.94 ± 0.17) and less with PoHI and Pe406 infusion (3.58 ± 0.58 and 3.26 ± 0.08, respectively; P < 0.05 vs Pe for both). Conclusions: Peripheral infusion of hepatopreferential insulin can achieve a metabolic profile that closely mimics portal insulin delivery, which reduces the risk of hypoglycaemia compared with peripheral insulin infusion.